FOOD AS A MEMORY TRIGGER: A STUDY OF LITERARY GASTRONOMY - Khoirunnisaa, Nabila; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The role of food in life is considered more than just sustenance; it also can convey emotions, evoke memories of the past, and create emotional bonds. Similarly, the function of food aspects in literature is significant. This research aims to explore the role of food towards characters in the anime "Isekai Izakaya: Koto Aitheria no Izakaya Nobu." The study employs a mimetic approach with a qualitative descriptive method, utilizing literary gastronomy as the main theory. The research material focuses on the anime "Isekai Izakaya: Koto Aitheria no Izakaya Nobu." The results of the analysis indicate that the role of food in this anime holds deeper significance beyond mere sustenance for its characters. Food carries profound symbolic meaning, particularly in illustrating memories. It acts as a mirror of the characters’ past within the narrative, representing specific experiences or memories like sadness, nostalgia, negative recollections, and pleasant reminiscences.